Preconcentration and determination of metal ions from fuel ethanol with a new 2,2'-dipyridylamine bonded silica - Vieira, Eduardo G. [UNESP]; Soares, Isaac V. [UNESP]; Dias Filho, Newton L. [UNESP]; da Silva, Niléia C. [UNESP]; Garcia, Edemir F. [UNESP]; Bastos, Andréa C. [UNESP]; Perujo, Sérgio D. [UNESP]; Ferreira, Tamires T. [UNESP]; Rosa, André H. [UNESP]; Fraceto, Leonardo F. [UNESP] (Elsevier, 2013)
A silica surface chemically modified with [3-(2,2'-dipyridylamine) propyl] groups was prepared, characterized, and evaluated for its metal ion preconcentration in fuel ethanol. To our knowledge, we are the first authors who have reported the present modification on silica gel surface. The material was characterized using infrared spectra, scanning electronic microscopy, and 13C and 29Si solid-state NMR spectra. Batch and column experiments were conducted to investigate for metal ion removal from fuel ethanol. The results showed that the Langmuir model describes the sorption equilibrium data of the metal ions in a satisfactory way. From the Langmuir isotherms, the following maximum adsorption capacities (in mmolg -1) were determined: 1.81 for Fe(III), 1.75 for Cr(III), 1.30 for Cu(II), 1.25 for Co(II), 1.15 for Pb(II), 0.95 for Ni(II), and 0.87 for Zn(II). Thermodynamic functions, the change of free energy (ΔG), enthalpy (ΔH), and entropy (ΔS) showed that the adsorption of metal ions onto Si-Pr-DPA was feasible, spontaneous, and endothermic. The sorption-desorption of the metal ions made possible the development of a preconcentration and quantification method of metal ions in fuel ethanol. © 2012 Elsevier Inc.
Keywords: Adsorption; Determination method; Ethanol fuel; Preconcentration; Thermodynamic parameters; Adsorption capacities; Bonded silica; Chemically modified; Column experiments; Dipyridylamine; Fuel ethanol; Infrared spectrum; Langmuir isotherm; Langmuir models; Metal ion removal; Pre-concentration; Quantification methods; Scanning electronic microscopy; Silica gel surfaces; Silica surface; Solid state NMR; Sorption equilibria; Thermodynamic functions; Thermodynamic parameter; Chromium compounds; Desorption; Ethanol fuels; Iron compounds; Lead; Nuclear magnetic resonance spectroscopy; Silica; Silica gel; Silicon; Zinc compounds; Metal ions; alcohol; alkane derivative; carbon 13; chromium; cobalt; copper; iron; lead; metal ion; nickel; silicon dioxide; zinc; adsorption; chemical bond; chemical model; chemical modification; concentration (parameters); desorption; energy; enthalpy; entropy; feasibility study; infrared spectrometry; nuclear magnetic resonance spectroscopy; priority journal; quantitative analysis; scanning electron microscope; synthesis; thermodynamics